2019
DOI: 10.1111/jam.14260
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic utility of in‐house loop‐mediated isothermal amplification and real‐timePCRtargetingvirBgene for direct detection ofBrucella melitensisfrom clinical specimens

Abstract: Aims In this present study, the utility of a newly developed loop‐mediated isothermal amplification (LAMP) and real‐time PCR assays designed to amplify the virB gene region of Brucella melitensis was evaluated from human clinical specimens. Methods and Results Fifty‐four culture‐confirmed cases of brucellosis and 54 culture negative but clinically suspected cases of brucellosis were included in the study. Whole blood, serum and other nonblood specimens were collected and subjected to blood culture using automa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 23 publications
0
7
0
1
Order By: Relevance
“…in milk and consumption of non-pasteurized dairy products pose an increasing risk to human consumers. Furthermore, it has been reported that the developed loop mediated isothermal amplification (LAMP) is a rapid and specific diagnostic tool for early and direct identification of Brucella in clinical specimens (Patra et al 2019). In addition, several methods for the optimization of DNA extraction from milk to improve subsequent PCR analysis have been set up leading to the reliable detection of Brucella spp.…”
Section: Detection Methods and Identification Of Brucella Spp In Thementioning
confidence: 99%
“…in milk and consumption of non-pasteurized dairy products pose an increasing risk to human consumers. Furthermore, it has been reported that the developed loop mediated isothermal amplification (LAMP) is a rapid and specific diagnostic tool for early and direct identification of Brucella in clinical specimens (Patra et al 2019). In addition, several methods for the optimization of DNA extraction from milk to improve subsequent PCR analysis have been set up leading to the reliable detection of Brucella spp.…”
Section: Detection Methods and Identification Of Brucella Spp In Thementioning
confidence: 99%
“…Loop-mediated isothermal amplification (LAMP) of DNA as well as real-time PCR have been proved as significant, sensitive, quick and specific diagnostics for B. abortus and other Brucella spp. directly from clinical specimens (Karthik et al 2014b(Karthik et al , 2014c(Karthik et al , 2016Patra et al 2019). Real-time recombinase polymerase amplification (RPA) was developed targeting the bcsp31 gene and the sensitivity was found to be 94% (Qinet al 2019).…”
Section: Newer Tools and Modificationsmentioning
confidence: 99%
“…If the diagnosis is based solely on viral nucleic acid detection, the workload will be too heavy as there are a large number of suspected cases for testing. Due to uncontrolled factors during sample collection or storage, a false negative or positive results may occur ( Tanner et al, 2015 ; Lim et al, 2018 ; Kim et al, 2019 ; Patra et al, 2019 ; Corman et al, 2020 ; Zhang et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%